Effect of Syzygium Aromaticum on the Growth of Cancer Cells and Microbes - Sharma, Pankaj (My University, 2014)
Clove, the sun-dried unopened flower bud from the plant Syzygium aromaticum is a commonly used spice and food flavor. Clove oils, may play important roles in prevention and treatment of various cancers. The main constituents in clove are polypropenoids and include thymol, carvacol, cinnamaldyhyde, and eugenol. Eugenol, which accounts for the majority of the essential oil of the plant, has been well proven to possess antioxidant effects. clove has shown promise as chemo preventative and therapeutic agents in cancer. In vitro and in vivo study has reported to have anti-inflammatory and antitumorigenic properties in Syzygium aromaticum. Different solvents ( Hexane, Diethyl ether, Ethyl acetate, Ethanol, Acetone and aqueous) extracts were prepared based on varying polarity index. Each of these extracts have shown anticancer activity, but most pronounced effect was observed in hexane. The Hexane extract of clove showed an activity against cancer cells at a minimum concentration of 125µg/ml, and anticancer activity at a concentration 350µg/ml showed 50% inhibition (IC50) against MCF-7 cells. Clove buds extracts have shown strong antibacterial activities against Staphylococcus aureus, Bacillus cereus, Escherichia coli, and Pseudomonas aeruginosa and similarly shown a very good antifungal activity against Candida albicans (agar-well diffusion and minimum inhibitory concentration tests)
M.Sc. (DBTES)
Keywords: Syzygium aromaticum , Eugenol, PBMCs, MTT, MCF-7 cells